Synthesis of macrocyclic BODIPY dyes and comparison of photochemical, sonochemical and sono-photochemical properties - Gunes, Ferhan Kara; Unlu, Seda; Elmali, Fikriye Tuncel; Atmaca, Goknur Yasa; Erdogmus, Ali (SPRINGER INT PUBL AG, 2025)
Near-infrared (NIR) boron dipyrromethene (BODIPY) dyes have gained attention among various fields due to their intense absorption and emission in the NIR region. In addition to intense absorption in the NIR region, having properties such as high singlet oxygen quantum yield (Phi) and high molar extinction coefficient make them enable to use as photosensitizer in photodynamic therapy (PDT) and sono-photodynamic therapy (SPDT). In this study, two novel macrocyclic BODIPY derivatives including -OH and -NO2 at para position of meso substituent of BODIPY cores have been synthesized and their molecular structures were determined by FT-IR, H-1 NMR and MS spectroscopic methods. Photochemical, sonochemical, and sono-photochemical properties of the synthesized compounds were examined. Phi(Delta) values for sono-photochemical method were calculated as 0.86 for compound 1a and 0.98 for compound 2a. Despite the well-documented advantages of SPDT over standalone SDT or PDT in enhancing therapeutic efficacy, a comparative study assessing all three methods using BODIPY-based sensitizers has not yet been reported. This study fills that gap by demonstrating the ability of macrocyclic BODIPY derivative sensitizers including electron donor (-OH) and electron withdrawing (-NO2) groups at para position of meso substituent to increase singlet oxygen generation using the SPDT method.
Keywords: BODIPY; Photochemistry; Sonochemistry; Sono-photochemistry; Singlet oxygen; DERIVATIVES; THERAPY; PROBES; Chemistry